The relation between aggression and the living group climate in a forensic treatment unit for adolescents: a pilot study - de Decker, An (International journal of offender therapy and comparative criminology, 2018)
In the current study, the associations between inpatient aggression and the living group climate as perceived by the adolescents admitted to a forensic psychiatric treatment unit, are investigated based on carefully registered longitudinal data. Multilevel regression analyses revealed a significant inverse relation between the number and severity of aggressive incidents and the amount of support, as well as with the possibilities of growth perceived by the adolescents. No significant associations of aggression and the perception of repression or atmosphere are found. Our study reveals preliminary evidence for the relation between the prevalence of aggressive incidents and how the adolescents perceive social contextual factors in daily forensic treatment practices. Moreover, preliminary evidence that evidence-based treatment programs and psychiatric care have an important influence on experienced possibilities for growth and support and as such prevent institutional aggression, is found.